Continuidades y rupturas en las asunciones contemporáneas de la palabra crítica - Proyecto - Steimberg, Oscar (2015)
This research project entails the continuation of our previous analysis titled "Art References II: the norm and form in the reception processing of publications related to everyday aesthetics" (IUNA 2013 - 2014), and is oriented to circumscribe, describe and shape the changes of the critical discourse (in printed and electronic publications in Buenos Aires) related to the effects of the continuities and transformations on its currents settlements, art scene and media landscape. Given the inclusion of the critique component on each genre as the main feature of the current textual circulation, this research will mainly focus on meta-texts, with the objective of joint areas of that discourse related with works and texts differentiated for their social context and for the election of areas of aesthetic experience. For this purpose, we choose the analysis of the proposition or the critique component included on instances of the production and circulation of the visual arts and cinematographic and theater productions. In each case, we focus on the textual materials included with each product or the materials that are used for its circulation, and the curatorial and institutional instances in general.